The Relationship between Executive Outpatient and Human Rights Protection for BPJS Health Patients in RSUD KRMT Wongsonegoro Semarang - I Wayan Agus Setiawan; Budi Sarwo; Daniel Budi Wibowo (SOEPRA, 2018)
Health was very important to human beings and was protected by the state because to get health was part of human rights, and it should be protected by the state. Health warranty was one of the protection forms provided by the government so that the rights to obtain health could be fulfilled. KRMT Wongsonegoro Hospital was a hospital that provided services to the patients of BPJS and organized executive and regular outpatients. The existence of two kinds of outpatients led to a necessity of seeing the protection to the patients getting social security in obtaining executive outpatient services.This research used a socio-legal approach having an analytical-descriptive specification. It would describe the implementation of the executive outpatient services and be then analyzed to see the relationship between the rights of the patients of Health BPJS and human rights protection.The results of the research showed that KRMT WongsonegoroHospital issued a Director’s Decree Nr. 290 of 2017 on Opening of Executive Outpatient of Gatotkaca and a Director’s Regulation Nr. 50 of 2017 on Executive Patient Cost Package. KRMT Wongsonegoro Hospital had not been able to thoroughly schedule specialist and subspecialist doctors for executive outpatients. For the time being KRMT Wongsonegoro Hospital did not take any additional cost for executive outpatient services.